ACCESS TO JUSTICE AS A COMPONENT OF THE RULE OF LAW UNDER MARTIAL LAW - Shvachka, Victoria (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
Purpose: to study the main challenges faced by a person in exercising his or her constitutional right of access to justice under martial law and to identify the main ways of overcoming them Aspects of exercising a person’s right of access to justice under martial law. Research methods: in the course of preparing the article, the author used a system of philosophical, general scientific and special methods. In particular, in order to study the international experience of legal regulation of the right of an individual to access to justice and its consolidation at the level of national legislation, the author used the systematic and comparative legal methods of scientific research. The structural-functional method made it possible to define more clearly the content of the concept of "access to justice" as a component of the rule of law. Results: The article highlights the main aspects of the implementation of the individual’s right of access to justice under martial law; analyses the content of the concept of "access to justice"; identifies the main challenges faced by the judicial system under martial law and explores the main ways of their solution; establishes that the main unresolved problem today is the frequent and prolonged disconnection of judicial institutions from the power supply, which results in the effective suspension of their activities, which leads to the violation of procedural deadlines and which, in essence, constitutes a violation of the principle of the rule of law.